Test-Retest and Inter-Rater Reliability Study of the Schedule for Oral-Motor Assessment in Persian Children - Manijeh Zarei Mahmood Abadi; Fariba Yadegari; Mehrzad Mehdizade; Enayatollah Bakhshi (Iranian Rehabilitation Journal, 2018)
Objectives: Reliable and valid clinical tools to screen, diagnose, and describe eating functions and dysphagia in children are highly warranted. Today most specialists are aware of the role of assessment scales in the treatment of affected individuals. However, the problem is that the clinical tools used might be nonstandard, and worldwide, there is no integrated assessment performed to assess the aforementioned conditions. In a previous study, we translated and examined the schedule for oral-motor assessment for its content validity. Therefore, in this study, we aimed to investigate the test-retest and inter-rater reliability of the schedule for oral-motor assessment. Methods: In this validation project, 23 children (6-48 month-old) who were referred to the imaging center were recruited. The assessment was based on the schedule for oral-motor assessment and was conducted by two speech-language pathologists for an inter-rater agreement evaluation. A retest was completed on 13 children up to 7 days. Intraclass Correlation Coefficient (ICC), kappa coefficient, and percentage of agreement were analyzed by using SPSS software (version 17). Results: We found a moderate Intraclass Correlation Coefficient (ICC=0.48) and a relatively sensible kappa coefficient (K=0.50) for test-retest agreement. Two speech-language pathologists reached 91% agreement on normal-dysfunctional decisions of schedule for oral-motor assessment. Sections 2, 3, 4, and 6 of schedule for oral-motor assessment demonstrated an agreement of 100%, and Sections 1 and 5 demonstrated an agreement of 91%. Discussion: Schedule for oral-motor assessment meets moderate levels of test-retest and inter-rater reliability criteria. Nonetheless, the percentage of decision consistency for inter-rater and test-retest examination turned out to be excellent.